Market value coverage (4A) in terms of fast food adoption - Nezakati, Hossein; Ali, Noor Azman; Asgari, Omid (Academic Journals, 2012)
This study explored the elements of market value coverage (MVC) (awareness, acceptability, accessibility and affordability) as applied to adoption diffusion of innovations. Reviewed of these factors as consumer-focused marketing concept were other important aspects of this study. Statistical tools in this research were analysis of variance and post HOC test. This research found market value coverage elements pattern in hierarchical situation according to social sub systems (innovators, early adopters, early majority, late majority and laggards) and provided two main distinct clusters: innovators and early adopters (acceptability, accessibility, awareness, and affordability) and the other one as; early majority, late majority, and laggards (acceptability, accessibility, affordability, and awareness). Acceptability was the main important Market Value Coverage element for all social sub systems.